Seizure in later life: an ode to the elderly - Sibia, Raminderpal Singh; S, Amith Kumar; Sharma, Honey (International Journal of Research in Medical Sciences, 2017)
Background: Seizure disorder and epilepsy are one of the common presenting symptoms to an emergency department for geriatric population. Cerebrovascular accident, metabolic derangement, trauma, neurodegenerative diseases, tumor, infections and psychiatric illnesses add up to the frequent etiological spectrum of seizure in elderly. Objective of current study was to describe clinical and etiological spectrum of seizures in later life. Methods: This retrospective study was conducted from medical records of 227 cases of elderly subjects presenting with seizure to emergency department, during a period of 3 years (2010-2013). Results: Most common age group involved was 65-75 years. Mean age of subjects included in the study was 68.13 ± 23.38 years. The most common etiology was cerebrovascular disorders 132 (58.14%), followed by CNS tumor in 16 (07.04%), hypoglycemia in 14 (06.16%), infections 14 (06.16%), substance abuse 12 (05.28%) and trauma 10 (04.40%). The most common presentation was with focal seizures, with 119 (52.42%) subjects whereas 82 (36.12%) presented with generalized tonic clonic seizure, 20 (08.81%) with generalized tonic seizure and 05 (02.20%) with absence seizures. Conclusion: The present study aims at pointing out the different clinical features and etiologies of geriatric seizures, thereby lets the reader have a head start with the management of an elderly patient presenting with seizure.